INVENTARISASI CACING PARASIT PADA IKAN BANDENG (Chanos chanos) DI TAMBAK DESA KETAPANG KECAMATAN MAUK KABUPATEN TANGERANG PROVINSI BANTEN - Endang Juniardi; Mustahal Mustahal; Achmad Noerkhaerin Putra (JURNAL PERIKANAN DAN KELAUTAN, 2014)
Milkfish is one of famous fish with highly nutrition contents. They are easily found in the market, and its price is relatively cheap. Milkfish just like other animals, has never free from the threat of various parasites. The fishes are also known to be vulnerable to parasite infection. Several worms species of fishes often inhabit a single body of fish. Therefore, in this study the inventory of parasite was done in milkfish. The examination was begun by measuring the fish total length and its weight, and then observed all the parasites found and inventoried. The examination also performed on the digestive tract by dissecting the fish. The whole organ observed and stored in a petridish containing a physiological saline solution. And then thy were observed by using a microscope. The results showed that were 6 types digenea 1 (5 species), Nematodes 1 (20 species), Procamallanus (3 species), Anisakis (4 species), Dichelyne (1 species), and Rhabdochona (1 species) with a parasitic worm intensity by 32 . Highest intensity in fish Nematodes 1 by 20 and the lowest in fish Dichelyne , and Rhabdochona by 1 with a prevalence of parasitic worms by 40% . Highest parasite prevalence of digenea 1 by 12% and the lowest was 1 Nematodes, Dichelyne, Rhabdochona by 4% .Keyword: inventory, parasite worms, milkfish